Intravenous iron administration strategies and anemia management in hemodialysis patients. Issue 1 (6th September 2016) - Michels, Wieneke M.; Jaar, Bernard G.; Ephraim, Patti L.; Liu, Yang; Miskulin, Dana C.; Tangri, Navdeep; Crews, Deidra C.; Scialla, Julia J.; Shafi, Tariq; Sozio, Stephen M.; Bandeen-Roche, Karen; Cook, Courtney J.; et al.
Abstract : Background. The effect of maintenance intravenous (IV) iron administration on subsequent achievement of anemia management goals and mortality among patients recently initiating hemodialysis is unclear. Methods. We performed an observational cohort study, in adult incident dialysis patients starting on hemodialysis. We defined IV administration strategies over a 12-week period following a patient's initiation of hemodialysis; all those receiving IV iron at regular intervals were considered maintenance, and all others were considered non-maintenance. We used multivariable models adjusting for demographics, clinical and treatment parameters, iron dose, measures of iron stores and pro-infectious and pro-inflammatory parameters to compare these strategies. The outcomes under study were patients' (i) achievement of hemoglobin (Hb) of 10–12 g/dL, (ii) more than 25% reduction in mean weekly erythropoietin stimulating agent (ESA) dose and (iii) mortality, ascertained over a period of 4 weeks following the iron administration period. Results. Maintenance IV iron was administered to 4511 patients and non-maintenance iron to 8458 patients. Maintenance IV iron administration was not associated with a higher likelihood of achieving an Hb between 10 and 12 g/dL adjusted odds ratio (OR) 1.01 [95% confidence interval (CI) 0.93–1.09] compared with non-maintenance, but was associated with a higher odds of achieving a reduced ESA dose of 25% or more [OR 1.33 (95% CI 1.18–1.49)] and lower mortality [hazard ratio (HR) 0.73 (95% CI 0.62–0.86)]. Conclusions. Maintenance IV iron strategies were associated with reduced ESA utilization and improved early survival but not with the achievement of Hb targets.